Research in inscriptional palaeography (RIP). Tombstone lettering in Dumfries and Galloway - Thomson, George (Proceedings of the Society of Antiquaries of Scotland, 2006)
A comprehensive and detailed survey was made of lettering on all accessible tombstone inscriptions in Dumfries and Galloway. Using statistical and other analytical techniques, a large amount of data was extracted. From this, comparisons were made with data from the author's previous study of inscriptional lettering throughout Scotland. The distributions of a number of letterform attributes were mapped, in some instances revealing clear geographical trends. The interesting subregional groupings in Dumfries and Galloway identified in the initial national survey were confirmed when the comprehensive data were used, though the distinctions were not so clear-cut. The rise of three more or less distinct area profiles identified using 42 letterform attributes is likened to the development of a dialect or accent, not learned by imitation, but subconsciously acquired as a consequence of living in local divergent communities.